(untitled) (Dhaka University Journal of Applied Science and Engineering, 2024)
The exotic electromagnetic properties of metamaterials (MTM) can be utilized to meet the increasing demand for smaller, lighter, and more compact multiband antennas. As the resonant frequency is dependent on the aperture parameters of the antenna, metamaterials allow for the miniaturization and performance enhancement of antennas. In this paper, two novel designs of metamaterial loaded microstrip patch antennas are proposed. The first structure emphasizes the miniaturization of patch antennas with performance improvements. The second one deals with the multiband operation of metamaterial loaded antennas with wider bandwidth and improved performance. Compared to the conventional microstrip patch antenna (MPA), the proposed metamaterial loaded antenna has reduced the size by 75%, and antenna characteristics have also improved significantly. The proposed metamaterial antenna resonates at 2.45 GHz, the return loss is -26 dB, and a gain of 5.28 dB is achieved. The multiband antenna can be realized by etching different numbers of complementary split ring resonators in the ground plane. The model proposed with three split ring resonators (SRR) at the ground plane shows quad band operations and can be used in S-band and C-band simultaneously. The quad-band antenna resonates at 3.04 GHz, 3.42 GHz, 5.35 GHz, and 6.08 GHz with bandwidths of 78 MHz, 93 MHz, 167 MHz, and 185 MHz, respectively. The antennas are designed on an FR-4 substrate with a permittivity of 4.3. Nicolson-Ross-Weir (NRW) method has been employed for the extraction and verification of the metamaterial properties of the unit cells. Due to its ability to capture more energy, the reported antenna can be used as a wireless device as well as an RF energy harvesting device. DUJASE Vol. 8 (1) 1-12, 2023 (January)